2021
DOI: 10.1002/ppul.25400
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the COVID‐19 pandemic and lockdown on symptom control in preschool children with recurrent wheezing

Abstract: Introduction Preschool wheezers are at high risk of recurrent attacks triggered by respiratory viruses, sometimes exacerbated by exposure to allergens and pollution. Because of the COVID‐19 infection, the lockdown was introduced, but the effects on preschool wheezers are unknown. We hypothesized that there would be an improvement in outcomes during the lockdown, and these would be lost when the lockdown was eased. Materials and Methods Patients underwent medical visits before and after the COVID‐19 lockdown. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 11 publications
4
21
0
Order By: Relevance
“…Asthma symptom control was more frequently achieved during the only studied quarter (Q4-2020) which included a period of lockdown for non-essential workers and for middle and high schools. This is concordant with a study in which asthma control scores from 85 children increased during the lockdown (9).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Asthma symptom control was more frequently achieved during the only studied quarter (Q4-2020) which included a period of lockdown for non-essential workers and for middle and high schools. This is concordant with a study in which asthma control scores from 85 children increased during the lockdown (9).…”
Section: Discussionsupporting
confidence: 91%
“…Though this study focuses on LFT results, it would be interesting to compare the trends of exacerbations in asthmatic patients to the number of hospital admission during this period. A recent study showed that hospital admissions for asthma were significantly lower during lockdown, suggesting a reduction not only of mild, but also of severe exacerbations (9).…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that, according to a validated questionnaire to assess asthma control in paediatrics, 4 most of them (87.7%) maintained good asthma control during isolation. As with similar recently published findings, 5 the high rates of well-controlled asthma observed could be related to different reasons: better therapeutic adherence, lower circulation of respiratory viruses (mainly rhinovirus) because of lockdown measures and improvement in air quality.…”
supporting
confidence: 87%
“…However, these reports are related to different populations of children and employed a different methodology. Nicola Ullmann et al 15 reported similar results regarding decreased wheezing episodes, recurrent wheezing (>3 episodes), bronchodilators, systemic steroid use, and ER admissions. However, this study refers to children 2–5.9 years old with a history of recurrent wheezing.…”
Section: Discussionmentioning
confidence: 77%
“…Three lockdowns and strict restrictions led to a dramatic reduction in health care utilization and presentations to the emergency room (ER) among children of all age groups. [15][16][17][18][19][20][21][22][23][24][25] Observing the COVID-19 restrictions, increases hygiene and decreases exposure to other infectious agents. In addition, lockdowns have the potential to reduce exposure to wheezing triggers such as viral infections, environmental pollution, exercise, and smoke.…”
mentioning
confidence: 99%